The Influence of Social Media on Arabic Language Learning Among Grade 8 Students at MTs Darussalam Singgar - Moh. Nasrul Hamdi; M. Alwasiti Rahman; M. Supriadi; Muh. Umar Tsani; Dewi Asmawati (Journal of Education, Teaching, and Learning, 2026)
The rapid development of digital technology has transformed the way students learn, particularly through the widespread use of social media as an interactive learning tool. This study aimed to examine the influence of social media on Arabic language learning among Grade 8 students at MTs Darussalam Singgar, with a focus on learning outcomes, motivation, and engagement. A quantitative approach with a correlational design was employed. The population consisted of all students, with a sample of 26 students selected using purposive sampling. Data were collected through questionnaires and documentation, and analyzed using descriptive statistics, Pearson correlation, and regression analysis. The results revealed that social media had a significant positive influence on Arabic language learning, with a correlation coefficient of 0.621 and a contribution of 38.6% to students’ learning outcomes. Social media was found to enhance students’ motivation, particularly intrinsic motivation, and increase engagement in learning activities. Furthermore, mediation analysis indicated that motivation partially mediated the relationship between social media and student engagement. The findings also showed that social media was more effective in improving receptive skills such as vocabulary and listening, while productive skills remained moderate. However, challenges such as distraction and lack of structured use were identified. In conclusion, social media serves as an effective and meaningful tool in Arabic language learning when used strategically and supported by proper guidance. This study highlights the importance of integrating social media into instructional practices to enhance students’ motivation, engagement, and learning outcomes in the digital era.